Volatile Fatty Acid Recovery from Simulated Digestate by Stripping - Simeone Chianese; Angelo Fenti; Giovanni Falco; Valentina Innocenzi; Marina Prisciandaro; Pasquale Iovino; Dino Musmarra (Chemical Engineering Transactions)
Volatile Fatty Acids (VFAs) are essential building block chemicals with a significantly increasing market demand. However, their production is traditionally based on non-renewable petrochemical sources, causing severe adverse health and environmental effects. The recovery of VFAs from organic substrates matches the need to approach a circular economy, which includes resource recovery, reuse and recycling. This work aimed to recover VFAs from simulated digestate by using an innovative and sustainable approach consisting of gas stripping followed by absorption. Gas stripping is based on separating volatile compounds from fermented broth or process streams through its interaction with the water-saturated gas phase. The proposed approach aims to be a breakthrough technology focused on the clean production of raw materials. Experimental investigations were performed on a lab scale to recover VFAs from a water solution by considering a single acid and a mix of acids. Moreover, the process simulation was carried out to validate the stripping step and the thermodynamic model to scale up the technology.